Distance matrix and Wiener Index of a new class of nanostar dendrimers - Ashrafi A.R.; Karbasioun A. (Utilitas Mathematica, 2011)
Let G be a graph. The Wiener index of G is defined as the sum of all pair wise distances of vertices of G. In this paper, the exact formula for the Wiener index of a new class of dendrimer nanostars is given.